PEMANFAATAN ARSIP RESEP DALAM EVALUASI PERBANDINGAN PERESEPAN OBAT ANTIHIPERTENSI GENERIK DAN BERMEREK PADA PASIEN RAWAT INAP DI RS ISLAM SITI HAJAR MATARAM TAHUN 2025 - Muhammad Aditya Rachman; Muhammad Habibullah Aminy; Lale Ajeng Khalifatun Wardani; Slamet Mardiyanto Rahayu (Nusadaya Journal of Multidiciplinary Studies, 2026)
Prescription archives play an essential role in supporting healthcare evaluation, particularly in analyzing drug utilization patterns. This study aims to evaluate the comparison between generic and branded antihypertensive drug prescriptions based on prescription archive data of inpatients at Siti Hajar Islamic Hospital Mataram in 2023. The research employed a descriptive method with a retrospective approach using archival document analysis. The results showed that generic drug prescriptions were more dominant than branded drugs, reflecting the implementation of cost-efficiency policies and rational drug use within the National Health Insurance system. However, branded drugs were still prescribed in certain clinical conditions. From an archival perspective, well-managed prescription records enable accurate, systematic, and accountable analysis of drug utilization patterns. This study highlights the importance of archival management in improving healthcare service quality and decision-making processes.